A Localized Complex of Two Protein Oligomers Controls the Orientation of Cell Polarity - Adam M. Perez (American Society for Microbiology, 2017)
ABSTRACT Signaling hubs at bacterial cell poles establish cell polarity in the absence of membrane-bound compartments. In the asymmetrically dividing bacterium Caulobacter crescentus, cell polarity stems from the cell cycle-regulated localization and turnover of signaling protein complexes in these hubs, and yet the mechanisms that establish the identity of the two cell poles have not been established. Here, we recapitulate the tripartite assembly of a cell fate signaling complex that forms during the G1-S transition. Using in vivo and in vitro analyses of dynamic polar protein complex formation, we show that a polymeric cell polarity protein, SpmX, serves as a direct bridge between the PopZ polymeric network and the cell fate-directing DivJ histidine kinase. We demonstrate the direct binding between these three proteins and show that a polar microdomain spontaneously assembles when the three proteins are coexpressed heterologously in an Escherichia coli test system. The relative copy numbers of these proteins are essential for complex formation, as overexpression of SpmX in Caulobacter reorganizes the polarity of the cell, generating ectopic cell poles containing PopZ and DivJ. Hierarchical formation of higher-order SpmX oligomers nucleates new PopZ microdomain assemblies at the incipient lateral cell poles, driving localized outgrowth. By comparison to self-assembling protein networks and polar cell growth mechanisms in other bacterial species, we suggest that the cooligomeric PopZ-SpmX protein complex in Caulobacter illustrates a paradigm for coupling cell cycle progression to the controlled geometry of cell pole establishment. IMPORTANCE Lacking internal membrane-bound compartments, bacteria achieve subcellular organization by establishing self-assembling protein-based microdomains. The asymmetrically dividing bacterium Caulobacter crescentus uses one such microdomain to link cell cycle progression to morphogenesis, but the mechanism for the generation of this microdomain has remained unclear. Here, we demonstrate that the ordered assembly of this microdomain occurs via the polymeric network protein PopZ directly recruiting the polarity factor SpmX, which then recruits the histidine kinase DivJ to the developing cell pole. Further, we find that overexpression of the bridge protein SpmX in Caulobacter disrupts this ordered assembly, generating ectopic cell poles containing both PopZ and DivJ. Together, PopZ and SpmX assemble into a cooligomeric network that forms the basis for a polar microdomain that coordinates bacterial cell polarity.